(untitled) (Stavební obzor - Civil Engineering Journal, 2017)
Wind loading is critical for the large-span and light-weight structures, and field measurement is the most effective way to evaluate the wind resistance performance of a specific structure. This study investigates the wind characteristics and wind-induced vibration on a sea-crossing bridge in China, namely Donghai Bridge, based on up to six years of monitoring data. It is found that: (1) there exists obvious discrepancy between the measured wind field parameters and the values suggested by the design code; and the wind records at the bridge site is easily interfered by the bridge structure itself, which should be considered in interpreting the measurements and designing structural health monitoring systems (SHMS); (2) for strong winds with high non-stationarity, a shorter averaging time than 10-min is preferable to obtain more stable turbulent wind characteristics; (3) the root mean square (RMS) of the wind-induced acceleration of the girder may increase in an approximately quadratic curve relationship with the mean wind speed; and (4) compared to traffic load, the wind dominates the girder’s lateral vibration amplitude, while the heavy-load traffic might exert more influence on the girder’s vertical and torsional vibrations than the high winds. This study provides field evidence for the wind-resistant design and evaluation of bridges in similar operational conditions.